The Influence of Instagram Social Media Promotion on Purchasing Decisions at Gallery RJ Store among Economic Education Students at Muhammadiyah University of Bengkulu - Venda Wintari; Milla, Hilyati; Kalsum, Ummi (CV. Generasi Insan Rafflesia, 2025)
The purpose of this study is to determine whether there is a significant influence of Instagram social media promotion at Toko Gallery RJ on the purchasing decisions of students majoring in Economic Education at the University of Muhammadiyah Bengkulu. This study involves two variables: Instagram social media promotion (independent variable/X) and purchasing decision (dependent variable/Y). The population consists of 115 students, and the sample includes 35 students from the Economic Education program, spanning cohorts of 2021, 2022, 2023, and 2024. Data collection methods used in this research include observation, questionnaires, and documentation. The data were analyzed quantitatively using IBM SPSS version 25 software. Analysis techniques involved calculating the mean and conducting a simple linear regression. The average score for Instagram social media promotion was 42.68, which falls within the interval of 43–45 and is categorized as very good. Similarly, the average score for purchasing decisions was 42.68, also within the interval of 43–45, and categorized as very good. The results indicate that there is a significant influence of Instagram social media promotion on purchasing decisions at Toko Gallery RJ among Economic Education students at the University of Muhammadiyah Bengkulu. This is supported by the results of the simple linear regression analysis, where the t-count value of 8.396 is greater than the t-table value of 2.042 (8.396 > 2.042). Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted, indicating that Instagram social media promotion significantly influences purchasing decisions.